Content Analysis of The Diagrammatic Representations of Primary Science Textbooks - Liu, Y.; Khine, Myint Swe (Eurasia Publishing House, 2016)
Science education research emphasizes the irreplaceable value of textbooks in students’ acquisition of scientific knowledge. Illustrations such as diagrams contained in science books are crucial modes of visual representations that facilitate learners’ conceptual learning. Through classifying, coding, and analysing diagrams from twenty science textbooks and workbooks used by Bahrain primary science curriculum, the aim of the study is to find out the distributional pattern and illustration characters of different diagrammatic types in the Bahrain’s primary science books. Descriptive statistical analysis was carried out. A one-way ANOVA test was performed to check if there are any distributional differences between textbook and workbook categories. Findings of the study summarized the characteristics of diagrammatic usage in the Bahrain primary science books. The textbook analysis method used in the research also provided some insights for researchers interested in analysing the usage of diagrams and other illustrations in science learning contexts.